Social wasps (Vespidae, Polistinae) in a Cerrado agrosystem in the state of Minas Gerais, southeastern Brazil - Dutra Barbosa, Leonardo; de Castro Jacques , Gabriel; Magalhães de Souza, Marcos (Revista Agrogeoambiental, 2022)
The survey and identification of social wasps, mainly in predominantly agricultural environments, is the first step to identify the ideal species to be used in biological pest control programs. The present work aims to inventory the social wasp fauna in an agrosystem in the Cerrado, Minas Gerais and identify species with potential to be used in biological control. Through active search, 478 wasps of 8 genera and 17 species were collected. The dominance of some species such as Protopolybia sedula, Polybia ignobilis, Polybia paulista, Polybia fastidiosuscula and Polybia occidentalis reinforces the importance of these species in agricultural environments and their potential use in biological pest control. In addition, this work confirms that some species of social wasps benefit from the anthropized environment, such as Polistes versicolor, which uses human constructions for nesting.